Socioeconomic studies of high-level nuclear waste disposal. - White, G F (1994)
The socioeconomic investigations of possible impacts of the proposed repository for high-level nuclear waste at Yucca Mountain, Nevada, have been unprecedented in several respects. They bear on the public decision that sooner or later will be made as to where and how to dispose permanently of the waste presently at military weapons installations and that continues to accumulate at nuclear power stations. No final decision has yet been made. There is no clear precedent from other countries. The organization of state and federal studies is unique. The state studies involve more disciplines than any previous efforts. They have been carried out in parallel to federal studies and have pioneered in defining some problems and appropriate research methods. A recent annotated bibliography provides interested scientists with a compact guide to the 178 published reports, as well as to relevant journal articles and related documents.